A System Dynamics Model for Biodiesel Industry in Indonesia - Arrumaisho, Ummu Sulaim; Sunitiyoso, Yos (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. The biggest demand for energy in Indonesia is oil fuels. To fulfill this demand, Indonesia has to import oil fuels. In order to decrease oil import, Government of Indonesia develop some policies to use biodiesel. Since 2009, biodiesel production in Indonesia has increased every year. To find out what factors and how these factors affect biodiesel industry’s growth in Indonesia, this research was conducted using literature study and system dynamics modeling. In this research, the factors that were evaluated are feedstock, biodiesel price, and government mandatory and regulation. The evaluation was carried out through system dynamics modeling for the next thirty years. The results of the system dynamics modeling simulation show that the factor that most influence the profit and biodiesel capacity construction is the use of advanced technology that can produce biodiesel from low quality and low-cost feedstocks. The second factor is government incentives in the form of a carbon tax that can increase the profit. The next factor is the amount of mandatory mixing of biodiesel in diesel oil. While biodiesel price factor did not significantly affect the profit and biodiesel capacity construction.Keywords: Biodiesel, causal loop diagram, industry, stock and flow diagram, system dynamics